Medium and large-sized mammals in a private reserve of natural heritage in the municipality of Jaú, São Paulo, Brazil - Reale, Ricardo; Fonseca, Renata Cristina Batista [UNESP]; Uieda, Wilson [UNESP] (Pensoft Publishers, 2014)
Medium and large-sized mammals control invertebrate and vertebrate populations and are important seed dispersers. These animals are losing their territory and living range due to deforestation and the fragmentation of natural areas, particularly in the Atlantic Forest and Cerrado. The Private Reserve of Natural Heritage (PRNH) Amadeu Botelho is isolated from other forest fragments and is thus a wildlife refuge in the region of Jaú, central-western region of state of São Paulo, southeastem Brazil. Animals as such as the puma (Puma concolor), ocelot (Leopardus pardalis) and jaguarundi (Puma yagouaroundi) have been sighted in the reserve by wildlife guards and residents. This reserve, which belongs to “Santo Antônio dos Ipês” farm, is surrounded by several plantations, and is very close to the center of the city of Jaú. In addition to surveying the mammal species in the reserve, this study diagnosed the influence of the farm’s activities and the proximity to the center of the municipality of Jaú on the fauna under study
Keywords: Mammalia